Tannin extraction from bark of rhizophora mucronata using soxhlet and boiling techniques - Ahmad Hafizan, Muhammad Muhayyidin; Nurul Aimi, Ghazali; Noor Fitrah, Abu Bakar; Wan Asma, Ibrahim; Arina, Sauki; Zulkafli, Hassan (Indonesian Society for Knowledge and Human Development, 2018)
Extraction of tannin Rhizophora Mucronata barks by using two methods, which were soxhlet extraction and boiling were demonstrated in this study in order to evaluate the effective technique for extraction. Several parameters such as the type of solvent used, time of extraction, and sample size were specified. The extractant was then evaporated using vacuum rotary evaporator. The percentage of extractives and the characterization of condensed (Stiasny Index) and hydrolyzable tannins were all quantified. The milled barks with different sizes were introduced to the extraction using water, methanol, acetone, and toluene as a solvent for three, six and nine hours for Soxhlet extraction while for boiling only water were used as a solvent and at four, six and eight hours. Results demonstrated that extraction from the bark of Rhizophora Mucronata with water for six and nine hours extracted approximately 29 wt% and 13wt % for both soxhlet extraction and boiling respectively when coupled with vacuum rotary evaporator. The Soxhlet extraction method was superior as compared to boiling. The optimum parameters for the Soxhlet extraction were water as the solvent at six hours extraction with 0.5 mm of milled bark particles size that extracted 29 wt% of extractives. The condensed tannin and hydrolyzable tannin of the extractives using soxhlet extraction were approximately 76 wt% and 0.00133 wt% respectively.